11 √3 - 3 √3 √4
= 11 √3 - 3*2 √3
= 5√3
Math pre cal 11
(11√3 - 3√12)^2 without using calculator
4 answers
Still has to be squared
(5√3)^2
= 25*3
= 75
(5√3)^2
= 25*3
= 75
( 11 √3 - 3 √12 )² = [ 11 √3 - 3 ∙ √ (3 ∙ 4 ) ]² = ( 11 √3 - 3 ∙ √ 3 ∙ √ 4 )² =
( 11 √3 - 3 ∙ √ 3 ∙ 2 )² = ( 11 √3 - 6 √ 3 )² = ( 5 √ 3 )² = 5² ∙ √ 3² = 25 ∙ 3 = 75
( 11 √3 - 3 ∙ √ 3 ∙ 2 )² = ( 11 √3 - 6 √ 3 )² = ( 5 √ 3 )² = 5² ∙ √ 3² = 25 ∙ 3 = 75
Factor out sqrt 3:
(sqrt3*(11-6))^2,
(sqrt3*5)^2 = 75.
(sqrt3*(11-6))^2,
(sqrt3*5)^2 = 75.